Active group-based performing arts interventions in Parkinson’s disease: an updated systematic review and meta-analysis - Maxwell S Barnish; Rebecca V Nelson-Horne; Sarah E Reynolds (BMJ Open)
Objectives To assess the evidence for active group-based performing arts interventions for people with Parkinson’s disease (PD).Setting Scholarly literature (published in English) from any country or countries (last search February 2025). This systematic review was not registered and received no funding.Data sources Five bibliographic databases: AMED (Ebsco), APA PsycINFO (Ovid), CINAHL (Ebsco), EMBASE (Ovid) and MEDLINE (Ovid), plus supplementary searches.Primary and secondary outcome measures Eligible studies used a quantitative design to assess the benefit of active group-based performing arts interventions on quality of life, functional communication, speech, motor function and cognitive status in PD. The risk of bias was assessed using the SURE, University of York Centre for Reviews and Dissemination and Newcastle-Ottawa Scale checklists. Data were synthesised using narrative synthesis and random-effects meta-analysis.Results A total of 94 studies were included: 2453 people with PD (mean age 68 years, 55% male) from 18 countries. Narrative synthesis supported nine combinations of performing arts modalities and outcome domains, including a benefit for dance on motor function (supported by 50 out of 54 studies), dance on quality of life (supported by 24 out of 37 studies) and singing on speech (supported by 17 out of 20 studies). Meta-analysis supported five combinations of performing art modalities, comparators and outcomes, including a clinically significant benefit for PD-specific dance versus usual care PDQ-39, MD −7.81, 95% CI −11.87 to −3.75 and tango-based dance versus usual care on UPDRS-III, MD −9.89, 95% CI −16.65 to −3.13.Conclusions Evidence from both the narrative synthesis and the meta-analysis supports a benefit for some combinations of performing arts modalities and outcomes. Limitations of the evidence base included differences in comparators and outcomes, heterogeneity, lack of control arms and male underrepresentation. Future studies should compare the effectiveness of different performing arts modalities, assess functional communication and consider clinical significance.